2024
DOI: 10.1007/s00431-024-05503-9
|View full text |Cite
|
Sign up to set email alerts
|

Autonomic cardiac function in children and adolescents with long COVID: a case-controlled study

A. B. Delogu,
C. Aliberti,
L. Birritella
et al.

Abstract: Although the mechanisms underlying the pathophysiology of long COVID condition are still debated, there is growing evidence that autonomic dysfunction may play a role in the long-term complications or persisting symptoms observed in a significant proportion of patients after SARS-CoV-2 infection. However, studies focused on autonomic dysfunction have primarily been conducted in adults, while autonomic function has not yet been investigated in pediatric subjects. In this study, for the first time, we assessed w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 34 publications
0
2
0
Order By: Relevance
“…All together, these events may possibly be the cause of the abnormal cardiovascular efficacy we documented at the CPET of children with LC. These data would suggest that the recognition of specific subphenotypes at CPET (eg, suggestive of dysautonomia) can suggest the need to assess heart rate variability, as we have documented in a previous case report and in a larger original study 13 , 36 and recognize syndromes associated with inappropriate tachycardia, which are potentially treatable, also in children. 41 Obviously, more studies are needed to validate our observations.…”
Section: Discussionmentioning
confidence: 60%
See 1 more Smart Citation
“…All together, these events may possibly be the cause of the abnormal cardiovascular efficacy we documented at the CPET of children with LC. These data would suggest that the recognition of specific subphenotypes at CPET (eg, suggestive of dysautonomia) can suggest the need to assess heart rate variability, as we have documented in a previous case report and in a larger original study 13 , 36 and recognize syndromes associated with inappropriate tachycardia, which are potentially treatable, also in children. 41 Obviously, more studies are needed to validate our observations.…”
Section: Discussionmentioning
confidence: 60%
“…Studies in adults, in fact, found that cardiac autonomic dysregulation is a major cause of exercise intolerance, leading to findings of cardiovascular limitation at CPET. 35 In another study, 36 we documented significant differences in heart rate variability of children with LC compared with controls. Modulation of the HR during exercise is a dynamic process tightly regulated by the autonomic nervous system and its imbalance may manifest during exercise as chronotropic incompetence or inadequate HR recovery.…”
Section: Discussionmentioning
confidence: 80%